2020
DOI: 10.1007/s40119-020-00191-6
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines Targeting PSCK9 for the Treatment of Hyperlipidemia

Abstract: Despite progress in both primary and secondary prevention, cardiovascular diseases (CVD) are still the largest group of ailments contributing to morbidity and mortality worldwide. Atherosclerotic changes, the primary pathological substrate for CVD, are closely related to hypercholesterolemia. Therefore, the treatment of hypercholesterolemia is a key therapeutic strategy for CVD management. Statins, as the gold standard in the treatment of hypercholesterolemia, have shown enhanced cardiac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Studies have shown that gain-of-function mutations of PCSK9 cause hyperlipidemia and early onset coronary heart disease, whereas loss-of-function mutations result in low plasma cholesterol levels and protection against coronary heart disease without apparent negative consequences. PCSK9 interacts with LDLR epidermal growth factor-like repeat A domain and induces its lysosomal degradation, thereby regulates plasma cholesterol levels. Therefore, inhibition of PCSK9 is being pursued as an approach to reduce plasma LDL cholesterol and TG levels. , …”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that gain-of-function mutations of PCSK9 cause hyperlipidemia and early onset coronary heart disease, whereas loss-of-function mutations result in low plasma cholesterol levels and protection against coronary heart disease without apparent negative consequences. PCSK9 interacts with LDLR epidermal growth factor-like repeat A domain and induces its lysosomal degradation, thereby regulates plasma cholesterol levels. Therefore, inhibition of PCSK9 is being pursued as an approach to reduce plasma LDL cholesterol and TG levels. , …”
Section: Discussionmentioning
confidence: 99%
“…Peptide-based vaccines have so far shown promising results in mice or macaques, including the use of bacteriophage virus-like particles displaying PCSK9-derived peptides ( 204 , 205 ). Whether vaccination against PCSK9 using modified lipid nanoparticles ( 206 ) or effective capsid-like particles ( 207 ) expressing full-length PCSK9 will be approved to treat severe pathologies will have to be carefully evaluated for any harmful side effects of such an irreversible therapy ( 163 ).…”
Section: Future Strategies Beyond Mab and Sirnamentioning
confidence: 99%
“…Although vaccination is mainly used as a prophylactic strategy for infectious diseases, there is growing interest in the use of vaccines for preventing noninfectious diseases, such as cardiovascular disease. In mice, vaccines targeting PCSK9 were shown to markedly lower plasma LDL-C levels [ 37 ]. In response, a number of phase 1 human clinical trials with PCSK9 vaccine have been completed or initiated [ 38 ].…”
Section: Pharmacological Strategies For Angptl3 Inactivationmentioning
confidence: 99%